Implementing peer to peer technology for ISE virtual community knowledge sharing / Shafizol Bakhtiar Mokhtar - Mokhtar, Shafizol Bakhtiar (2006)
Knowledge sharing is a method of sharing information between community members or between other communities. Nowadays, knowledge sharing could not be implemented between student and lecturers and student to student. That is because, student did not have an appropriate platform for them to share their opinion, share their knowledge among themselves and to their lecturers. Beside that the problem of workspace and space acquired over internet also contributing to the unavailability of sharing knowledge between student and lecturers. By using peer to peer technologies, a new platform for sharing data between lecturers and student could be created. With the limitation for storage is almost did not happen, folder for data could be easily customize, peer to peer provide the most flexible data sharing and migration to be implemented. This paper will suggest the peer to peer technologies and how it could be implemented in ISE Virtual Community.